2017
DOI: 10.1103/physreve.96.022410
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative response and clustering: Consequences of membrane-mediated interactions among mechanosensitive channels

Abstract: Mechanosensitive (MS) channels are ion channels which act as cells' safety valves, opening when the osmotic pressure becomes too high and making cells avoid damage by releasing ions. They are found on the cellular membrane of a large number of organisms. They interact with each other by means of deformations they induce in the membrane. We show that collective dynamics arising from the inter-channel interactions lead to first and second-order phase transitions in the fraction of open channels in equilibrium re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(53 reference statements)
0
0
1
Order By: Relevance
“…Previous continuum models suggested that, due to hydrophobic mismatch, membrane-mediated interactions between rigid, cylindrically symmetric, MSCs will lead to their collective opening [41][42][43]. This is not what we observe.…”
contrasting
confidence: 95%
“…Previous continuum models suggested that, due to hydrophobic mismatch, membrane-mediated interactions between rigid, cylindrically symmetric, MSCs will lead to their collective opening [41][42][43]. This is not what we observe.…”
contrasting
confidence: 95%